BEBERAPA PANDANGAN MENGENAI ISLAM DARI PERSPEKTIF PARTI POLITIK MELAYU - Abdul Hamid, Faisal@Ahmad Faisal; Jalani, Hamidah (Journal of Al-Tamaddun, 2010)
After a long development in the history of Malay Archipelago, Islam was able to raise the distinction of the Malays as a nation that was well-known throughout the world. However the development was affected due to several internal and external elements that hinder the process. The arrival of Western colonization had established a new framework of thought among the Malay intellectuals in their effort to translate and implement Islam in daily lives. This paper attempts to look at the growth of Islamic influence in the Malay starting from the initial arrival until the birth of two Malay political parties, with their own self-perceptions in translating their Islamic understanding in societal life or state matters.